Doped, Defect-Enriched Carbon Nanotubes as an Efficient Oxygen Reduction Catalyst for Anion Exchange Membrane Fuel Cells - Chuyen Van Pham; Britton, Benjamin; Boehm, Thomas; Holdcroft, Steven; Thiele, Simon (Advanced Materials Interfaces, 2018)
Bond polarization of doped atoms and carbon and lattice defects are considered important aspects in the catalytic mechanisms of oxygen reduction reaction (ORR) on heteroatom-doped carbon catalysts. Previous work on metal-free catalysts has focused either on bond polarization or lattice defects. Here multi-heteroatom doped defect-enriched carbon nanotubes (MH-DCNTs) that combine both effects to enhance ORR activity are designed. Lattice defects in MH-DCNTs are enriched by unzipping and length-shortening of carbon nanotubes, and also by creating carbon vacancies via decomposition of doped F atoms. Electrochemical analysis using rotating disc electrode voltammetry shows that the ORR kinetic current density of MH-DCNT increases with lattice-defect density, the latter of which is verified by Raman spectroscopy, while the onset potential increases with annealing temperatures. An optimized MH-DCNT ORR catalyst exhibits a half-wave potential of 0.81 V versus reversible hydrogen electrode and limiting current density of 5.0 mA cm−2 at an electrode rotation speed of 1600 rpm in 0.1 m KOH. Further, it is demonstrated that MH-DCNT, as a cathode catalyst layer in an anion exchange membrane fuel cell (AEMFC), delivers a peak power density of 250 mW cm−2, which is ≈70% the performance of an AEMFC using a conventional Pt/C catalyst.
CRIS-Team Scopus Importer:2023-03-29
Keywords: anion exchange polymer electrolyte; fuel cells; heteroatom doped carbon nanotubes; metal free catalyst; oxygen reduction reaction